Discrepancies Between Legal Norms and Practices in the Protection of Notaries - Santoso, Roni Joyo; Hamid, Adnan (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
This study examines the legal protection afforded to notaries in the execution of their official duties, particularly in the context of criminal legal proceedings. Utilizing a normative legal approach and detailed case analysis, the research reveals that the current legal protection mechanisms for notaries remain suboptimal, largely due to the inadequate enforcement of Article 66 of the Notary Law. The frequent criminalization of notaries is attributed to ambiguous distinctions between ethical breaches, administrative violations, and criminal offenses. Although the Notary Honorary Council (MKN) is designated to serve as an initial filter in such matters, its role is frequently overlooked by law enforcement agencies. This study advocates for the strengthening of the MKN’s authority, the development of integrated procedural guidelines, and the harmonization of relevant laws and regulations to ensure more effective and equitable legal protection for notaries. The findings aim to inform future legal reforms focused on safeguarding the integrity of the notary profession.